Chemical analysis of food : techniques and applications - Pico, Yolanda (Waltham, MA : Academic Press, 2012)
'The book contains twenty three chapters written by experts on the subject is structured in two parts: the first one describes the role of the latest developments in analytical and bioanalytical techniques, and the second one deals with the most innovative applications and issues in food analysis. The two first introductory chapters about sampling technique, from basic one to the most recent advances, which is still a food challenge because is responsible of the quality and assurance of the analysis, and on data analysis and chemometrics are followed by a review of the most recently applied techniques in process (on-line) control and in laboratories for the analysis of major or minor compounds of food. These techniques ranged from the non-invasive and non-destructive ones, such as infrared spectroscopy, magnetic resonance and ultrasounds, to emerging areas as nanotechnology, biosensors and electronic noses and tongues, including those already well-established in food analysis, such as chromatographic and electrophoretic techniques. These chapters also include two important tools for solving problems in chemical and biological analysis such as mass spectrometry and molecular-based techniques'--
Includes bibliographical references and index.
Keywords: Food -- Analysis; Food -- Composition